Kinetic aspects of rat (Rattus-norvegicus albinus) submandibular glands lactic-dehydrogenase - Sassaki, K. T.; Rosa, C. D.; Cesar, M. D.; Rosa, R. (Inst Tecnologia Parana, 1994)
Submandibular glands of male rats were homogenized with 33 mM sodium potassium phosphate buffer, pH 6.5, containing 1 mM MgCl2 and 0.1 mM DTT and purified with ammonium sulphate, phosphocellulose chromatography, eluted with KC1 0.5 M, followed by Blue Sepharose CL-6B chromatography, eluted with NADH 0.5 mM. The enzyme kepts stable for 60 days when stored at -15-degrees-C in 33 mM phosphate buffer. In other experiment the enzyme was purified by oxamate-agarose chromatography from a crude extract of submandibular gland and the results obtained were better than by phosphocellulose and Sepharose CL-6B chromatography. The Km values for pyruvate. NADH, lactate and NAD+ were established. Sodium oxamate at 0.1 and 0.9 mM concentrations inhibited the LDH activity by 40 and 85%, respectively (competitive); with sodium oxalate the inhibition was of 30% (uncompetitive) and with 3-acetyl pyridine adenine dinucleotide was 80%.
Keywords: LACTIC DEHYDROGENASE; SUBMANDIBULAR GLAND; SALIVARY GLAND